ROLE OF FOOD MANAGEMENT SYSTEMS ON FOOD SAFETY IN HOTELS - Mutua, Alfred (Journal of Food Sciences, 2021)
Purpose: Food is an essential part of life, but if it is contaminated it can cause illness even death, and food can be contaminated with toxic substances from outside or even it is already in the food itself. Food safety synonymous with food hygiene embracing anything in the processing, preparation or handling of food to ensure it is safe to eat. The general objective of the study was to the study was to establish role of food management systems on food safety in hotels. Methodology: The paper used a desk study review methodology where relevant empirical literature was reviewed to identify main themes and to extract knowledge gaps. Findings: The study found out that application of standard food safety systems, compliance to food safety system and implementation of food safety system impact the provision of safe food in hotels. Recommendations: The study recommends that that application of standard food safety systems led to the provision of safe food in hotels. The study recommends that all hotels meet requirements to ensure the safety of foods. The proliferation of laws and regulations to food safety management system standards are the response to concerns of the hotel management. Developments in food safety regulation spark a move towards a more strict approach to food safety. A range of laws, acts, regulations, norms and directives addressing a variety of different aspects in food hygiene, should be enforced by relevant authorities